2020
DOI: 10.1021/acsfoodscitech.0c00045
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Antinutrient Composition and Heavy Metal and Phenolic Profiles of Maize (Zea mays) as Affected by Different Processing Techniques

Abstract: The effect of processing on the proximal, amino acid, micro-and macromineral, heavy metal, vitamin, antinutrient, and phenolic profiles of maize (Zea mays) was investigated using standard techniques. Boiling decreased the total amino acid content unlike frying and roasting, but they did not affect the total phenolic content of maize. Boiling increased the levels of moisture, phosphorus, and vitamin B12; depleted selenium; and decreased the levels of phytate, saponin, calcium, sodium, iron, zinc, copper, and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This increase in the total phenolic content could be a result of the release of the bound form of the phytochemicals in the corn bran during the frying process. 41 The report of Fang et al 42 showed a similar result where the total phenolic content of cooked sausages was higher than that of fresh sausages. The increase was attributed to the probability that mild cooking conditions could have led to the partial release of the phenolic compounds in the sugarcane fiber.…”
Section: Resultsmentioning
confidence: 78%
“…This increase in the total phenolic content could be a result of the release of the bound form of the phytochemicals in the corn bran during the frying process. 41 The report of Fang et al 42 showed a similar result where the total phenolic content of cooked sausages was higher than that of fresh sausages. The increase was attributed to the probability that mild cooking conditions could have led to the partial release of the phenolic compounds in the sugarcane fiber.…”
Section: Resultsmentioning
confidence: 78%
“…Metabolic fingerprinting of methanol extracts of maize grain using UHPLC coupled with mass spectrometry (MS) detection, which combines high-resolution mass spectrometry (HRMS) and multistage mass spectrometry (MS 2 and MS 3 fragmentation), identified a total of 90 compounds (Supplementary Table 1). The identity of 16 compounds (compounds 1, 5, 9, 12, 14, 21, 25, 26, 32, 66-68, 76, 87, 89, 90) were confirmed by direct comparison with appropriate standards, while the identity of the remaining 74 compounds were obtained after examination of MS data (exact mass and specific fragmentation), in consultation with the available literature on LC/MS and nuclear magnetic resonance (NMR) analysis of maize metabolites (Li et al, 2018;Zhou et al, 2019;Lux et al, 2020;Eleazu et al, 2021). Basic retention and MS data, as well as references confirming the presence and, in some cases, mass fragmentation of specific compounds in maize are listed in Supplementary Table 1.…”
Section: Metabolomics Lc/ms Metabolic Fingerprinting Of Maize Grainmentioning
confidence: 94%
“…In a study using corn, heat treatments managed to reduce various antinutrients such as phytate, saponin compounds, trypsin inhibitor, including heavy metals such as selenium, although not statistically significant. 108 Additionally, conventional cooking and microwave heating of vegetables led to a significant decrease of polyphenol content. 73,109,110 Surprisingly, roasting and extrusion apparently did not alter polyphenol content in one study using buckwheat flour.…”
Section: Acs Foodmentioning
confidence: 99%
“…It is argued, however, that various heat-related preprocessing treatments such as blanching and roasting tend to increase the degradation of vitamins. , However, heat treatments such as blanching, roasting, and frying managed to modulate approximate contents, mineral compositions, and antinutrients. In a study using corn, heat treatments managed to reduce various antinutrients such as phytate, saponin compounds, trypsin inhibitor, including heavy metals such as selenium, although not statistically significant . Additionally, conventional cooking and microwave heating of vegetables led to a significant decrease of polyphenol content. ,, Surprisingly, roasting and extrusion apparently did not alter polyphenol content in one study using buckwheat flour .…”
Section: Overview Of Functional Properties and Product Applicationsmentioning
confidence: 99%
See 1 more Smart Citation